Outcomes of social assistance in Central and Eastern Europe: A pre-transfer post-transfer comparison - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2013)
The poverty reduction potential of national social assistance programs in eight Central and Eastern European countries is examined using data from the EU-SILC. Results indicate that social assistance programs are a marginal component of the social protection system throughout the region. They serve small populations, spend relatively little compared to needs and the benefits they award are largely a top-up for their clients. However, the more extensive and liberal programs achieve higher effectiveness in reducing poverty. Unlike Western Europe, no trade-off between extensiveness and benefit generosity or between generosity and efficiency could be found. Decentralization and discretion are associated with inefficiency and arbitrariness in entitlement decisions rather than improved targeting.
Keywords: D31; H23; I32; I38; 330; social assistance; redistribution; poverty; Central and Eastern Europe